Correlation between Maximum Clot Firmness in FIBTEM and Fibrinogen Level in Critical Trauma Patients - Supphamongkhon Khunakanan; Osaree Akaraborworn; Burapat Sangthong; Komet Thongkhao (Critical Care Research and Practice)
Background. Both fibrinogen level and rotational thromboelastometry (ROTEM®) are accurate tests to demonstrate a bleeding tendency. FIBTEM® is one type of ROTEM test to determine the function of fibrinogen. An advantage of FIBTEM is helping physicians make proper decisions for blood component transfusions. However, the correlation between fibrinogen level and FIBTEM is still unclear. Objective. The aim of this study was to demonstrate a correlation between maximum clot firmness (MCF) in FIBTEM and fibrinogen level in critical trauma patients. Methods. Data were retrospectively collected from 87 patients who visited the emergency department between May 2017 and January 2019 in Songklanagarind Hospital. Blood specimens were sent for both ROTEM evaluation and fibrinogen level. The data were analysed with STATA program version 12.1. Results. Eighty-seven patients were enrolled in the study over the 21-month period. The patients consisted of 73 males (83.9%) with a median age of 40 years. Seventy-three patients (83.9%) were still alive. The following equation from FIBTEM MCF was used to predict fibrinogen level: fibrinogen level = 138 + (15.2 × FIBTEM MCF) (Lin’s concordance correlation coefficient of 0.52, P<0.001). The results showed a good correlation of FIBTEM MCF to predict patients with hypofibrinogenemia (area under ROC curve = 0.81). Patients with normal fibrinogen levels received significantly fewer units of all types of blood components. Conclusion. FIBTEM MCF had poor prediction of fibrinogen level; however, it can help to identify patients who have hypofibrinogenemia.